Anomia across the atypical AD phenotypic spectrum. (31st December 2021) - Eustace, Ana; Wong, Bonnie; Quimby, Megan; Dickerson, Brad C.; Putcha, Deepti
Abstract: Background: Visual naming is impaired in AD, most prominently in the typical late‐onset amnestic and logopenic variant Primary Progressive Aphasia (lvPPA) syndromes. However, little is known about how patients with these or other AD syndromes (Posterior Cortical Atrophy; PCA, and early‐onset amnestic dysexecutive) perform on auditory confrontation naming tests that do not rely on visual perception of stimuli. Performance on such tests may be of particular relevance to measuring anomia in PCA, who present with visual cognitive deficits. The present study analyzes Auditory Naming Test (ANT) performance across the atypical AD phenotypic spectrum. Method: Fifty‐three patients (19 PCA, 13 lvPPA, 21 amnestic dysexecutive) were administered the ANT. Total uncued correct responses and total correct responses with phonemic cues were analyzed. Performance differences between groups were evaluated using one‐way ANOVA. Independent samples t‐tests were performed to verify between‐group differences. Result: Uncued auditory naming was impaired across all atypical AD groups, with group differences observed (F(2, 50)=10.31, p<0.001) such that the lvPPA group (60% correct) performed most poorly followed by the amnestic dysexecutive group (77% correct; t=2.09, p=0.04). PCA patients performed best (91% correct; lvPPA < PCA, t=5.5, p<0.001; amnestic dysexecutive < PCA, t=2.5, p=0.02). Auditory naming after phonemic cuing also differed across groups (F(2, 50)=6.15, p=0.004): lvPPA (76% correct), amnestic dysexecutive (81% correct), and PCA (97% correct). Performance was still impaired in lvPPA and amnestic dysexecutive groups after cuing, but were comparable to each other (p > 0.6), while PCA patients performed better than lvPPA (t=4.5, p=0.001) and amnestic dysexecutive (t=2.7, p=0.03) groups, falling within normal limits. Conclusion: Auditory naming was most impaired in lvPPA but improved with phonemic cues. In contrast, cues did not greatly improve performance in the amnestic dysexecutive group, suggesting either a goal‐directed retrieval deficit or semantic knowledge loss. PCA patients demonstrated mild word retrieval deficits in the absence of visual stimuli, potentially reflecting auditory‐verbal working memory deficits previously identified in the literature. However, the PCA group improved with phonemic cuing, suggesting intact semantic knowledge. We plan to build on these results by next examining the cognitive contributors to and regional atrophy correlates of ANT performance in each group.